2021
DOI: 10.4018/ijepr.20210701.oa4
|View full text |Cite
|
Sign up to set email alerts
|

Framework for Smart City Model Composition

Abstract: This paper is a reflective overview of the knowledge on online conversion of services in the perspective of urban planning. It points that traditional planning aimed at building optimal spatial relationships between particular functions in urban environment. Appropriate decision-making rules had been introduced, contributing to a hierarchical land-use structure. This conventional approach has been recently challenged by the rapid ICT development which added a lively, virtual, non-spatial dimension of urban eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, “according to Wiyono and Nurmandi (2022), smart cities and intelligent transportation have several important aspects, including development, management, and planning. These aspects also focus on development planning, transportation system development, environmental management, and local government planning, including intelligent city planning and thoughtful transportation planning.” Of course, planning is needed to build optimal spatial relationships between certain functions in urban environments and government areas (Chun et al, 2021). Several concepts are essential for innovative city projects, such as city buildings with intelligent services, smart hospitals, smart traffic, smart factories, and transportation (Xiaoyi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, “according to Wiyono and Nurmandi (2022), smart cities and intelligent transportation have several important aspects, including development, management, and planning. These aspects also focus on development planning, transportation system development, environmental management, and local government planning, including intelligent city planning and thoughtful transportation planning.” Of course, planning is needed to build optimal spatial relationships between certain functions in urban environments and government areas (Chun et al, 2021). Several concepts are essential for innovative city projects, such as city buildings with intelligent services, smart hospitals, smart traffic, smart factories, and transportation (Xiaoyi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These changes can occur in part of a land management process or by means of a complete overhaul and replacement of a specific land management process. In essence, smart land management complements the traditional land management processes by establishing omnichannel services (i.e., enterprises that use both online and offline channels for communicating and distributing their products) [31]. In addition to smart technologies application, smart land management relies on citizens that have the capacity to utilize information technology to advance their courses of actions and interests in a more efficient manner.…”
Section: Smart Land Management and Blockchain Technologymentioning
confidence: 99%
“…The analysis of a number of publications participating in the sample showed that a smart city includes the active use of information and communication technologies and is aimed at meeting the needs of its residents, providing them with a safe and comfortable living environment [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Fig 1 Publication Activity Of the Researchers For The Keyword "Smart City" According To The Scopus Databasementioning
confidence: 99%